Annexin A2 in Virus Infection - Taylor, Julia R.; Skeate, Joseph G.; Kast, W. Martin (Frontiers in Microbiology, 2018)
Viral life cycles consist of three main phases: 1) attachment and entry, 2) genome replication and expression, and 3) assembly, maturation, and egress. Each of these steps is intrinsically reliant on host cell factors and processes including cellular receptors, genetic replication machinery, endocytosis and exocytosis, and protein expression. Annexin A2 (AnxA2) is a membrane-associated protein with a wide range of intracellular functions and a recurrent host factor in a variety of viral infections. Spatially, AnxA2 is found in the nucleus and cytoplasm, vesicle-bound, and on the inner and outer leaflet of the plasma membrane. Structurally, AnxA2 exists as a monomer or in complex with S100A10 to form the AnxA2/S100A10 heterotetramer (A2t). Both AnxA2 and A2t have been implicated in a vast array of cellular functions such as endocytosis, exocytosis, membrane domain organization, and translational regulation through RNA binding. Accordingly, many discoveries have been made involving AnxA2 in viral pathogenesis, however the reported work addressing AnxA2 in virology is highly compartmentalized. Therefore, the purpose of this review is to provide information regarding the role of AnxA2 in the lifecycle of multiple epithelial cell-targeting viruses to highlight recurrent themes, identify discrepancies, and reveal potential avenues for future research.